Racecadotril Versus Loperamide for Acute Diarrhea of Infectious Origin in Adults: A Systematic Review and Meta‐Analysis - Maryam Aziz; Laiba Urooj Malik; Erum Javed; Syeda Zuha Sami; Muhammad Maaz; Muhammad Arham Khan; Muhammad Farmaan; Omer Farooq; Umer Iqbal; Aashish Kumar; Syed Ali Arsal; Shafin Bin Amin; et al. (Health Science Reports)
ABSTRACT Background and Aims Loperamide and racecadotril are two antidiarrheal medications with different mechanisms of action that are highly important for the treatment of diarrhea as a result of infectious pathology. Acute infectious diarrhea has a profound impact on our surroundings because of its detrimental effects on individual health. Medication such as racecadotril, among various other drug classes, plays a pivotal role in treating these diseases via the management of symptoms through its antisecretory, proabsorptive effects on the intestinal tract. The main objective of this analysis was to evaluate and contrast the usefulness and safety profiles of these drugs by combining information from randomized controlled trials and highlighting important side effects reported, such as constipation and stomach discomfort. Method A total of 117 records were found after a thorough literature search was carried out across several databases, including PubMed, Google Scholar, and the Cochrane Library. The Cochrane Collaboration technique was utilized to evaluate the potential for bias. RevMan 5.2 data analysis was performed via a random effects model. The results are displayed as the mean difference (MD) with 95% CI for continuous data and relative risk (RR) with 95% confidence intervals (CIs) for dichotomous data. Statistical significance was established at p < 0.05. Results Compared with loperamide, racecadotril significantly improved the clinical response (relative risk [RR] and 95% confidence interval [CI]). Additionally, the analysis of secondary outcomes revealed varying effects on abdominal pain, constipation, and abdominal enlargement, with moderate heterogeneity observed (I² = 56%). Conclusion Compared with loperamide, racecadotril is a better therapeutic option for adult diarrhea caused by infection.